DIRECT COST OF TECHNOLOGIES FOR MANAGEMENT OF DEFINITIVE COLOSTOMY IN A SPECIALIZED SERVICE (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Objectives: To identify the direct cost of a specialized service with the use of collection equipment and adjuvants and to compare it with the simulated cost of intestinal self-irrigation in people with permanent colostomy. Method: Descriptive-exploratory study conducted through a quantitative approach in the form of multiple-case studies. The convenience sample consisted of 22 participants registered in a specialized service in the north of Minas Gerais, Brazil. Data collection was carried out in medical records from January 2019 to January 2020. Results: Among the participants, 59.1% had complications related to the ostomy and peristomal skin. Regarding collector/adjuvant equipment, the cost ranged from R$2,340.00 to R$5,535.00, average cost of R$4,050.01, and sample standard deviation of R$770.31.The average direct cost with colostomy self-irrigation was R$ 3,793.44. Conclusion: Theaverage direct cost of collection/adjuvant equipment was higher than that of colostomy self-irrigation, impacted by the presence of complications and the value of the colostomy protector.